Synthesis of a polyethylene glycolylated polysiloxane system through a two‐step procedure and its compatibility. Issue 34 (29th April 2019) - Liang, Hongping; Tang, Zilun; Feng, Minghui; Wu, Jianyu; Lin, Wenjing; Zu, Xihong; Zhang, Jie; Gu, Yuxin; Yi, Guobin
ABSTRACT: Acrylic macromonomer was synthesized by esterification of acrylic acid (AA) and PEGylated siloxane alcohol. And the acrylic macromonomer was employed as unsaturated precursor for the hydrosilylation with polymethylhydrosiloxane (PMHS). FTIR, 1 H, 13 C, 29 Si‐NMR, and TGA proved that PEGylated polysiloxane was successfully synthesized. The morphological studies revealed that the dimples in the cross sections were attributed to polyethylene glycol (PEG) phase domains with diameters of 5–15  μ m. The contribution of polar and dispersion factor toward surface energy was studied by contact angle (CA) measurement. The results showed that wetting behavior could transform from hydrophobic to hydrophilic with the CA from 122° to 54°. The final PEGylated polysiloxane provided sufficient compatibility and good wetting behavior, in contrast with silane ethers or alkyl silanes, indicating that it might be utilized as an alternate candidate for personal care. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47889. Abstract :